Expansion of myeloid derived suppressor cells correlates with number of T regulatory cells and disease progression in myelodysplastic syndrome. (1st February 2016) - Kittang, Astrid Olsnes; Kordasti, Shahram; Sand, Kristoffer Evebø; Costantini, Benedetta; Kramer, Anne Marijn; Perezabellan, Pilar; Seidl, Thomas; Rye, Kristin Paulsen; Hagen, Karen Marie; Kulasekararaj, Austin; Bruserud, Øystein; Mufti, Ghulam J.
Abstract : Although the role of CD4 + T cells and in particular Tregs and Th17 cells is established in myelodysplastic syndrome(MDS), the contribution of other components of immune system is yet to be elucidated fully. In this study we investigated the number and function of myeloid derived suppressor cells (MDSCs) in fresh peripheral blood and matched bone marrow samples from 42 MDS patients and the potential correlation with risk of disease progression to acute myeloid leukemia (AML). In peripheral blood, very low-/low risk patients had significantly lower median MDSC number (0.16×10 9 /L(0.03–0.40)) compared to intermediate-/high-/very high risk patients, in whom median MDSC counts was 0.52×10 9 /L(0.10–1.78), p < 0.005. When co-cultured with CD4+ effector T-cells (T-effectors), MDSCs suppress Teffector proliferation in both allogeneic and autologous settings. There was a positive correlation between the number of Tregs and MDSCs (Spearman R = 0.825, p < 0.005) in high risk and not low risk patients. We also investigated MDSCs' expression of bone marrow-homing chemokine receptors, and our data shows that MDSCs from MDS patients express both CXCR4 and CX3CR1 which might facilitate migration of MDSCs to bone marrow. Monocytic MDSCs(M-MDSCs) which are more frequent in the peripheral blood express higher levels of CX3CR1 and CXCR4 than the granulocytic subtype (G-MDSCs), and circulating M-MDSCs had significantly higher CX3CR1 expression compared to bone-marrow M-MDSCs in intermediate-/high-/very high risk MDS. Our results suggest that MDSCs contribute significantly to the dysregulation of immune surveillance in MDS, which is different between low and high risk disease. It further points at mechanisms of MDSCs recruitment and contribution to the bone marrow microenvironment.